Two dimensional and real-time three dimensional ultrasound measurements of left ventricular diastolic function after marathon running: results from a substudy of the BeMaGIC trial - Roeh, Astrid; Schuster, Tibor; Jung, Philip; Schneiders, Jens; Halle, Martin; Scherr, Johannes (International Journal of Cardiovascular Imaging, 2019)
Strenuous exercise results in transient but minor alterations in left ventricular diastolic function (LVDF). The aim of this study is to describe and interpret the kinetics of the well-established 2D parameters of diastolic function and the novel and very sensitive 3D parameters before/after a marathon race. LVDF was evaluated by transthoracic echocardiography (TEE) in 212 healthy male [aged 42 (36–49) years)] marathon runners (all Be-MaGIC-study) in the week prior to (V1), immediately after (V2), 24 h after (V3) and 72 h after (V4) a marathon race. Real time three-dimensional echocardiography (RT3DE) included maximal and minimal left atrium (LA) volume, total LA ejection fraction (Total-EF), total LA stroke volume (Total-SV), true ejection fraction (True-EF) and atrial stroke volume (ASV). After adjustment for possible confounders (heart rate and systolic blood pressure), 2D Parameters of left ventricular inflow (E/A-ratio) decreased from pre- to immediately post-race (− 0.3 ± 0.06, p < 0.001) and returned to baseline within 24 h. E/e′mean-ratio remained unchanged directly post-race, but was significantly increased during follow-up of 24 and 72 h. 3D LA Vmin was increased immediately postrace and in the 24 h follow-up, LA Vmax was increased immediately post-race and in the follow-up of 24 and 72 h. During follow-up of 72 h, but not immediately postrace, TrueEF and ASV were significantly increased. Both techniques revealed acute and prolonged alterations of diastolic LV function. Considering all parameters, the recovery of diastolic LV after a marathon seems to take longer than previously assumed. Trial registration ClinicalTrials.gov ID: NCT00933218.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac fatigue; Diastolic function; Echocardiography; Exercise; Marathon